Prevalence of Intraventricular Hemorrhage in Preterm Neonate - Saleem Ahmed, Qazi Mumtaz Ahmad, Habib Ullah, Furqan Saleem, Hassan Zubair, Sobia Al Rehman, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: This study was conducted to explore the incidence of Intraventricular Hemorrhage in preterm neonate. Method: The study was conducted in the neonatal unit of the department of Pediatrics. It included all the preterm neonates under 36 weeks of gestational age who were admitted in neonatology unit. The study included both male and female babies. The age of babies at time of admission was <24 hrs. Cranial USG was done at the age of 1, 3, and 7 days. Results: The incidence of IVH in these patients turned out to be 55%. According to age, patients less than 24hrs were 30(54.54%), patients between 24hrs to 72hrs were 17(30.90%) whereas patients between 72hrs to 7days were 7(12.72%). Conclusion: The incidence of IVH in these patients turned out to be 55%.